Self-tracking cycling data as representations of landscape. (3rd April 2019) - O'Neill, Shaleph J.
ABSTRACT: The representation of landscape has changed considerably in the arts since the nineteenth century. From the grand and sometimes fantastical paintings of the apocalyptic sublime, to the more topographically correct contemplative sublime; from the concern for light over form in impressionism, to the intensity of colour saturation in post-impressionism; from emotive expressionism to the fractured abstraction of cubism; from its evaporation in abstract expressionism and dematerialisation in conceptual art to its reclamation in walking art; from photographs taken on journeys, to objects found along the way; from words that capture a sense of place, to films that immerse us in those places; from room sized panoramas to virtual reality CAVEs. This paper aims to map out a contemporary typology of landscape representation. Specifically, it attempts to locate self-tracking data art as a new form of landscape representation, one that traverses a spectrum of imagery, from isomorphic representations of real places, through objective mapping of experience and on into the realm of abstracted subjectivity. In doing so it positions the author's own work within this wider context along side other artists that are engaged is similar practices.